2011
DOI: 10.1085/jgp.201110698
|View full text |Cite
|
Sign up to set email alerts
|

An extracellular domain of the accessory β1 subunit is required for modulating BK channel voltage sensor and gate

Abstract: A family of tissue-specific auxiliary β subunits modulates large conductance voltage- and calcium-activated potassium (BK) channel gating properties to suit their diverse functions. Paradoxically, β subunits both promote BK channel activation through a stabilization of voltage sensor activation and reduce BK channel openings through an increased energetic barrier of the closed-to-open transition. The molecular determinants underlying β subunit function, including the dual gating effects, remain unknown. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 45 publications
(117 reference statements)
1
30
2
Order By: Relevance
“…By contrast, our results do not support a role for the β-subunit loops in the modulation of VSDs, and clearly establish that the intracellular N terminus is responsible for VSD stabilization in BK, in the absence of Ca 2+ . Although our results appear to disagree with previous reports establishing a role for residues in the extracellular loop of β1 in VSD modulation (41,58), it is important to recall here the studies of the group of Cox (30,49), which reported that to fully account for the increase in apparent Ca 2+ sensitivity induced by the β1-subunit it was necessary that β1 also decrease the true Ca 2+ affinity to the closed channel. Moreover, Sweet and Cox (49) further studied this problem, and combining high-resolution Ca 2+ doseresponse curves together with mutagenesis of the two high-affinity Ca 2+ binding sites led to the conclusion that indeed the β1-subunit modifies Ca 2+ binding to the BK channel.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…By contrast, our results do not support a role for the β-subunit loops in the modulation of VSDs, and clearly establish that the intracellular N terminus is responsible for VSD stabilization in BK, in the absence of Ca 2+ . Although our results appear to disagree with previous reports establishing a role for residues in the extracellular loop of β1 in VSD modulation (41,58), it is important to recall here the studies of the group of Cox (30,49), which reported that to fully account for the increase in apparent Ca 2+ sensitivity induced by the β1-subunit it was necessary that β1 also decrease the true Ca 2+ affinity to the closed channel. Moreover, Sweet and Cox (49) further studied this problem, and combining high-resolution Ca 2+ doseresponse curves together with mutagenesis of the two high-affinity Ca 2+ binding sites led to the conclusion that indeed the β1-subunit modifies Ca 2+ binding to the BK channel.…”
Section: Discussioncontrasting
confidence: 99%
“…In fact, mutating conserved residues in the extracellular loop of β1 alters the G-V relationships (41,42), thus affecting both the equivalent charge as well as intrinsic channel activation (41). By replacing β1 external loop residues Y74 and Y105 by alanine and recording I g from BK channels coexpressed with these mutated β1s, we determined that these mutations did not alter the ability of β1 to shift chargemovement voltage dependence (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3), and together these results suggest that Vt3.1 inhibits voltage sensor movements or the coupling between the voltage sensor and the pore, or both, to inhibit voltage-dependent activation. It has been shown that the association of the ␤1, ␤2, and ␤4 subunit alters voltage sensor movements of slo1 (43), and the extracellular loop of the ␤1 subunit contributes to such modulations (44). The alteration of the ␤4 subunit extracellular loop by Vt3.1 alters voltage-dependent activation, indicating that the extracellular loop also contributes to the ␤4 modulation of mslo1 voltage-dependent gating mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…A functional conserved domain among β1, β2, and β4 subunits stabilize the active configuration of the channels, while increasing the energy barrier that separates closed from open states. 147 The importance of the β subunits is not only related to the modulation of Ca 2+ sensitivity and voltagedependent gating of the α subunit, but also to the fact that they act as a target "sites/receptors" for different agents that could modulate BK channel function, such as protein, toxins, blockers or openers. Consequently, their significance is also related to channel trafficking and expression in cellular surface.…”
Section: Bk Channel Auxiliary Subunitsmentioning
confidence: 99%